Use of trimethoprim- sulfamethoxazole for treating Pneumocystis jirovecii pneumonia in a patient with glucose-6-phosphate dehydrogenase deficiency: a case report - Wang, Linyu; Xie, Xianlong; Li, Zhe; Li, Yan (Frontiers in Medicine, 2024)
Background Pneumocystis jirovecii pneumonia (PJP) is an opportunistic infection caused by the yeast-like fungus P. jirovecii. As recommended by some guidelines, the first-line treatment for this infection is trimethoprim-sulfamethoxazole (TMP-SMX), and the second-line treatment includes drugs such as dapsone, pentamidine, primaquine, Atovaquone, clindamycin, and caspofungin. Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an X-linked gene disorder in which treatment with oxidizing drugs, such as sulfonamides, dapsone, primaquine, can directly destroy hemoglobin present in red blood cells (RBCs), thereby inducing methemoglobin and hemolysis. Case presentation Here, we present the case of a lymphoma patient with previous G6PD deficiency who was admitted to ICU for the treatment of severe pneumonia combined with respiratory failure. PJP was detected by the next-generation sequencing of the bronchoalveolar lavage fluid. The patient was initially treated with the antifungal drug caspofungin; however, this treatment showed poor therapeutic effect. Based on the evaluation of G6PD enzyme activity and the patient’s previous history of G6PD deficiency, we finally treated the patient with low-dose TMP-SMX combined with caspofungin and provided rigorous medical care to the patient. Following this treatment, the patient’s clinical symptoms improved, lung computed tomography showed reduced pulmonary inflammation, and the fungal β-(1,3)-D-glucan test (G test) showed decreased levels of fungal D-glucan. After 57 days, the TMP-SMX treatment was discontinued. No symptoms related to G6PD deficiency, such as hemolysis, hematuria, and anemia, occurred during the treatment course. Conclusion This is the first report mentioning the successful treatment of Pneumocystis jirovecii pneumonia with a double-drug regimen with low-dose TMP-SMX and caspofungin in a T-lymphoblastic leukemia/lymphoma patient with previous G6PD deficiency. Enzyme activity detection is the first step for anti-PJP treatment in patients with G6PD deficiency. Although patients with mild enzyme deficiency may not show any adverse reactions, we still recommend the regular monitoring of the levels of RBCs, hemoglobin, and hematocrit before and after the use of sulfonamides or sulfoxides and other oxidizing drugs in patients with G6PD deficiency. Among other things, early and correct diagnosis of Pneumocystis jirovecii pneumonia in hematological malignancies patients is very important. Relevant oncologists should be alert to the risk of Pneumocystis jirovecii pneumonia in these patients.